2019
DOI: 10.7759/cureus.6517
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Incidental Parathyroidecomy in Thyroid Surgery

Abstract: Background: Incidental parathyroidectomy with subsequent hypoparathyroidism and postoperative hypocalcemia is thought to be one of the common complications of thyroidectomy. Current literature reports wide discrepancy in incidence and risk factors.Objectives: The aim of our study was to evaluate the incidence and risk factors of incidental parathyroidectomy in thyroid surgery.Methods: A retrospective study included 270 patients who had thyroid surgery that was performed over two years from January 2017 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…17 This report found no association between gender and inadvertent parathyroidectomy, which is compatible with most other recent studies. 6,[8][9][10][11]14,16,17,[19][20][21][22]24,25 This study also found no association between age at surgery and inadvertent parathyroidectomy, in keeping with recent literature. 6,[9][10][11][12][13][14]17,19,[21][22][23] A retrospective review of 1114 thyroidectomies by Barrios et al 23 found that, on multivariable analysis, low-volume surgeons had a significantly higher incidence of inadvertent parathyroidectomy.…”
Section: Risk Factors For Inadvertent Parathyroidectomysupporting
confidence: 90%
See 3 more Smart Citations
“…17 This report found no association between gender and inadvertent parathyroidectomy, which is compatible with most other recent studies. 6,[8][9][10][11]14,16,17,[19][20][21][22]24,25 This study also found no association between age at surgery and inadvertent parathyroidectomy, in keeping with recent literature. 6,[9][10][11][12][13][14]17,19,[21][22][23] A retrospective review of 1114 thyroidectomies by Barrios et al 23 found that, on multivariable analysis, low-volume surgeons had a significantly higher incidence of inadvertent parathyroidectomy.…”
Section: Risk Factors For Inadvertent Parathyroidectomysupporting
confidence: 90%
“…Several factors may contribute to the wide variation in reported inadvertent parathyroidectomy rates. Many studies (including this report) included thyroid lobectomy in the analysis of inadvertent parathyroidectomy, 7,8,10,11,[13][14][15][16]18,20,21,[23][24][25] whereas others analyse only total or near-total thyroidectomy cases. 6,7,9,12,17,19,22 Some studies excluded patients undergoing re-operative thyroid surgery 18,20,21 or central neck dissection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incidental parathyroidectomy is considered a minor finding in final histopathology, but it is important for the thyroid surgeon to be able to identify the factors that increase the risk of incidental parathyroidectomy during thyroidectomy and exercise appropriate caution in these patients[ 24 ]. Despite the risk of unavoidable incidental pa-rathyroidectomy, careful dissection and meticulous intraoperative identification of PGs can reduce the incidence of incidental parathyroidectomy[ 25 ]. Although preservation of the surrounding vasculature and capsular dissection techniques are used to avoid incidental parathyroidectomy or disruption of the parathyroid vasculature, reliable tools to both identify and assess PGs during surgery, and to predict whether a patient will develop hypoparathyroidism, are limited[ 26 ].…”
Section: Discussionmentioning
confidence: 99%